Atomically dispersed manganese on graphene nanosheets as biocompatible nanozyme for glutathione detection in liver tissue lysate using microfluidic paper-based analytical devices - Baruah, Diksha J.; Thakur, Ashutosh; Roy, Esha; Roy, Kallol; Basak, Sumanjita; Neog, Dipankar; Bora, Himangsu K.; Konwar, Rituraj; Chaturvedi, Vikash; Shelke, Manjusha V.; Das, Manash R. (ACS Applied Materials & Interfaces, 2023)
Recently, single atom catalysts (SACs) featuring M-N-x (M = metal) active sites on carbon support have drawn considerable attention due to their promising enzyme-like catalytic properties. However, typical synthesis methods of SACs often involve energy-intensive carbonization processes. Herein, we report a facile one-pot, low-temperature, wet impregnation method to fully utilize M-N-4 sites of manganese phthalocyanine (MnPc) by decorating molecular MnPc over the sheets of graphene nanoplatelets (GNP). The synthesized MnPc@GNP exhibits remarkable peroxidase-mimic catalytic activity toward the oxidation of chromogenic 3,3 `,5,5(')-tetramethylbenzidine (TMB) substrate owing to the efficient utilization of atomically dispersed Mn and the high surface-to-volume ratio of the porous catalyst. A nanozyme-based colorimetric sensing probe is developed to detect important biomarker glutathione (GSH) within only 5 min in solution phase based on the ability of GSH to effectively inhibit the TMB oxidation. The high sensitivity and selectivity of the developed colorimetric assay enable us to quantitatively determine GSH concentration in different biological fluids. This work, for the first time, reports a rapid MnPc@GNP nanozyme-based colorimetric assay in the solid substrate by fabricating microfluidic paper-based analytical devices (mu PADs). GSH is successfully detected on the fabricated mu PADs coated with only 6.0 mu g of nanozyme containing 1.6 nmol of Mn in the linear range of 0.5-10 mu M with a limit of detection of 1.23 mu M. This work also demonstrates the quantitative detection of GSH in mice liver tissue lysate using mu PADs, which paves the way to develop mu PADs for point-of-care testing.
Keywords: colorimetricsensing; Glutathione; mu PADs; nanozyme; single atom catalyst; tissue lysate